DAILY ENGLISH SPEAKING : BERKOMUNIKASI DENGAN PERCAYA DIRI MENGGUNAKAN BAHASA INGGRIS - Natalia Faradheta Putri; Dholley Dwi Jatmiko Latabuo; Satya Candrasari; Jesica Angelina Antonia Turambi (LPPM UPN Veteran Jakarta, 2023)
Proficient in communicating using English is a must-have ability today. This was also realized by the orphanage supervisor of Yayasan Awam Bina Amal Sejati (ABAS), therefore non-academic provisions were given to all children of orphanage residents. However, cost constraints mean that not all children get the opportunity to hone their skills by taking courses. To help answer existing problems, a team of lecturers in Communication Science at Kalbis Institute of Technology and Business carried out community service programs at the ABAS Foundation by providing communication training, one of which was about daily English conversation. This activity begins with a discussion related to the material to be given to training participants, material delivery, and ends with an evaluation. Basically, the activities that have been carried out run smoothly and the enthusiasm of the participants in participating in the training is quite good. However, it is too early to judge that this activity was successful. The reason is that English is not an ability that can be mastered in an hour or two but requires a quite some time and intensive learning to master. In addition, sex education and photography topics are more interesting for the participants because they can practice using props. In addition, a native English speaker is considered to help the participants in familiarizing and practicing because exposure to native speakers is an opportunity that they rarely get. The two evaluation points above can be a precious input for the community service team in compiling materials in order to involve native speakers and use teaching aids to increase the interest and interest of trainees in the future.